Glycemic Control with Ipragliflozin, a Novel Selective SGLT2 Inhibitor, Ameliorated Endothelial Dysfunction in Streptozotocin-Induced Diabetic Mouse - Salim, Hotimah Masdan; Fukuda, Daiju; Yagi, Shusuke; Soeki, Takeshi; Shimabukuro, Michio; Sata, Masataka (Frontiers in Cardiovascular Medicine, 2016)
Background: Endothelial dysfunction caused by increased oxidative stress is a critical initiator of macro- and micro-vascular disease development in diabetic patients. Ipragliflozin, a selective sodium glucose co-transporter 2 (SGLT2) inhibitor, offers a novel approach for the treatment of diabetes by enhancing urinary glucose excretion. The aim of the present study was to examine whether ipragliflozin attenuates endothelial dysfunction in diabetic mice. Methods: Eight-week-old male C57BL/6 mice were treated with streptozotocin (150 mg/kg) by a single intraperitoneal injection to induce diabetes mellitus. At three days of injection, ipragliflozin (3 mg/kg/day) was administered via gavage for 3 weeks. Vascular function was assessed by isometric tension recording. Human umbilical endothelial cells (HUVEC) were used for in vitro experiments. RNA and protein expression were examined by quantitative RT-PCR (qPCR) and western blot, respectively. Oxidative stress was determined by measuring urine 8-hydroxy-2'-deoxyguanosine (8-OHdG) level. Results: Ipragliflozin administration significantly reduced blood glucose level (P<0.01) and attenuated the impairment of endothelial function in diabetic mice, as determined by acetylcholine-dependent vasodilation (P<0.001). Ipragliflozin did not alter metabolic parameters such as body weight and food intake. Ipragliflozin administration ameliorated impaired phosphorylation of Akt and eNOSSer1177 in the abdominal aorta and reduced reactive oxygen species generation as determined by urinary excretion of 8-OHdG in diabetic mice. Furthermore, qPCR analyses demonstrated that ipragliflozin decreased the expression of inflammatory molecules (e.g.; MCP-1, VCAM-1 and ICAM-1) in the abdominal aorta (P<0.05, respectively). In in vitro studies, incubation with methylglyoxal, one of the advanced glycation end products, significantly impaired phosphorylation of Akt and eNOSSer1177 (P<0.01, respectively) and increased the expression of MCP-1, VCAM-1, and ICAM-1 in HUVEC. Conclusion: Ipragliflozin improved hyperglycemia and prevented the development of endothelial dysfunction under a hyperglycemic state, at least partially by attenuation of oxidative stress.